Pengaruh Rasio Leverage dan Rasio Return On Assets (ROA) terhadap Tax Avoidance - Cika Tumbelina; Nunung Nurhayati (UNISBA Press, 2022)
Abstract. tax payments is a technique in reducing official tax payments and does not violate applicable laws and regulations. This research was conducted with the aim of understanding the impact on tax avoidance due to the ROA ratio with the level of leverage. Then use the population and samples from the annual budget archive (2017-2019) of the BUMN industry in the IDX data collection, which includes secondary data and from 20 industries 17 industries were selected as samples. In data processing apply descriptive, verification, and quantitative techniques. For the data analysis technique applying multiple linear regression, the hypothesis test applies the f test along with the t test. Then this research concludes that there is no impact between the leverage ratio and tax avoidance and there is an impact between ROA and tax avoidance. Abstrak. Menghindari pembayaran perpajakan merupakan teknik dalam mengurangi penyetoran perpajakan secara resmi dan tidak melanggar peraturan perundangan yang berlaku. Riset ini dilakukan dengan maksud memahami terkait dampak yang ditimbulkan pada sikap penghindaran pajak akibat adanya rasio ROA dengan tingkat leverage. Kemudian menggunakan population beserta sample dari arsip anggaran tahunan (2017-2019) industri BUMN pada pendataan BEI, yang mana data ini termasuk secondary data serta dari 20 industri dipilih 17 industri sebagai sample. Dalam pengolahan data menerapkan teknik deskriptif, verification, serta quantitative. Untuk teknik analisa data menerapkan regresi linier berganda, hypothesis test menerapkan uji f beserta uji t. Kemudian riset ini menghasilkan kesimpulan yaitu tidak adanya dampak antara rasio leverage dengan tax avoidance serta adanya dampak antara ROA dengan tax avoidance.